2022
DOI: 10.1371/journal.pone.0261518
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Female Community Health Volunteers (FCHVs) for cardiovascular diseases risk screening in Nepal

Abstract: Introduction Non-Communicable Diseases (NCDs) have become the leading public health problems worldwide and the cardiovascular diseases (CVDs) is one of the major NCDs. Female Community Health Volunteers (FCHVs) in Nepal are the key drivers to implementing frontline health services. We explored the potential for engaging FCHVs for CVD risk screening at the community level in Nepal. Methods We used multiple approaches (quantitative and qualitative) for data collection. The trained FCHVs administered CVD risk s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The potential of community health workers to screen community members using mHealth tool was recently assessed and proved in Kenya [14]. In the present study it was found that the observed agreement between the CHW-generated 10-year CVD risk characterization and the nurse-generated 10-year CVD risk characterization for either overall study participants, rural study participants, or urban study participants is fair, as the computed kappa statistics are in range of 0.21-0.40 [19], and statistical significance was observed only for overall study participants and rural study participants. These results are far lower than those found in Nepal where the agreement between CHV-generated 10-year CVD risk characterization and doctor-generated 10-year CVD risk characterization for either overall study participants, rural study participants, or urban study is substantial as the computed kappa statistics were in range of 0.61-0.80 [19], and were all statistically significant.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…The potential of community health workers to screen community members using mHealth tool was recently assessed and proved in Kenya [14]. In the present study it was found that the observed agreement between the CHW-generated 10-year CVD risk characterization and the nurse-generated 10-year CVD risk characterization for either overall study participants, rural study participants, or urban study participants is fair, as the computed kappa statistics are in range of 0.21-0.40 [19], and statistical significance was observed only for overall study participants and rural study participants. These results are far lower than those found in Nepal where the agreement between CHV-generated 10-year CVD risk characterization and doctor-generated 10-year CVD risk characterization for either overall study participants, rural study participants, or urban study is substantial as the computed kappa statistics were in range of 0.61-0.80 [19], and were all statistically significant.…”
Section: Discussionmentioning
confidence: 61%
“…For instance, one of the previous studies conducted in four countries-Bangladesh, Guatemala, Mexico, and South Africa-proved that trained CHWs successfully used non-laboratory tools to screen for cardiovascular disease risk and produced results that were highly congruent with those produced by trained health professionals (physicians and nurses) [3]. A recent study conducted in one of the low-income countries, Nepal, proved that community health volunteers (CHVs)-led CVD risk screening works and reported a concordance between CVD risk scores generated by CHVs and CVD risk scores generated by doctors [19]. It was also proved in regions of rural Kenya that CHWs can use mHealth tool to screen for CVD risk factors [14].…”
Section: Introductionmentioning
confidence: 95%
“…They are frontline workers in the Nepalese healthcare system and are trusted by community members. There are over 51,000 members in Nepal as of the end of 2020 (20). They can be trained in annual diabetic foot screening and foot education.…”
Section: Discussionmentioning
confidence: 99%
“…FCHV's role was noticeable during emergencies such as the 2015 earthquake and COVID-19 (Horton et al, 2020;Prajwal et al, 2020). Various research shows the scope of FCHV is to prevent noncommunicable diseases (Basnet et al, 2021;Rawal et al, 2022). Their title as volunteers renders them speechless against misuse.…”
Section: Role and Responsibilities Of Female Community Health Volunte...mentioning
confidence: 99%